Swastika - Unidentified artist (Colorado State University. Libraries, 2016)
Four swastikas created in the late 20th century.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Multicolor on a dark background.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama